Single-Stage Posterior Vertebral Column Resection With Circumferential Reconstruction for Thoracic/Thoracolumbar Burst Fractures With or Without Neurological Deficit: Clinical Neurological and Radiological Outcomes. Issue 5 (June 2022) - Hamzaoglu, Azmi; Elsadig, Mustafa; Karadereler, Selhan; Mutlu, Ayhan; Akman, Yunus Emre; Ozturk, Huseyin; Aslantürk, Okan; Sanlı, Tunay; Kahraman, Sinan; Enercan, Meric
Study Design: Retrospective study. Objective: The aim of this study is to evaluate the clinical, neurological, and radiological outcomes of posterior vertebral column resection (PVCR) technique for treatment of thoracic and thoracolumbar burst fractures. Methods: Fifty-one patients (18 male, 33 female) with thoracic/thoracolumbar burst fractures who had been treated with PVCR technique were retrospectively reviewed. Preoperative and most recent radiographs were evaluated and local kyphosis angle (LKA), sagittal and coronal spinal parameters were measured. Neurological and functional results were assessed by the American Spinal Injury Association (ASIA) Impairment Scale, visual analogue scale score, Oswestry Disability Index, and Short Form 36 version 2. Results: The mean age was 49 years (range 22-83 years). The mean follow-up period was 69 months (range 28-216 months). Fractures were thoracic in 16 and thoracolumbar in 35 of the patients. AO spine thoracolumbar injury morphological types were as follows: 1 type A3, 15 type A4, 4 type B1, 23 type B2, 8 type C injuries. PVCR was performed in a single level in 48 of the patients and in 2 levels in 3 patients. The mean operative time was 434 minutes (range 270-530 minutes) and mean intraoperative blood loss was 520 mL (range 360-1100 mL). The mean LKA improved from 34.7° to 4.9° (85.9%). For 27 patients, the initial neurological deficit (ASIA A in 8, ASIA B in 3, ASIA C in 5, and ASIA D in 11) improved at least 1 ASIA grade (1-3 grades) in 22 patients (81.5%). Solid fusion, assessed with computed tomography at the final follow-up, was achieved in all patients. Conclusion: Single-stage PVCR provides complete spinal canal decompression, ideal kyphosis correction with gradual lengthening of anterior column together with sequential posterior column compression. Anterior column support, avoidance of the morbidity of anterior approach and improvement of neurological deficit are the other advantages of the single stage PVCR technique in patients with thoracic/thoracolumbar burst fractures.